?FACTORS AFFECTING CHROMIUM REMOVAL USING SACCHAROMYCES CEREVISIAE (Biological Sciences - PJSIR, 2000)
The removal of chromium ions Cr(lll) from aqueous solutions using S cerevisiae was studied. The influence of some factors affecting biosorption activity such as temperature, pH, weight of dried cells, concentration of Cr(III), time contact between biomass and metal and shaking were examined. Maximum uptake level of Cr (TIl) ions was attained by using 350 mg biomass and 100ug Cr(lll), in 0.2M phosphate buffer (pH 8.0), 25°C, shaking at 200 pm.